Notes on the distribution of Cyperus ohwii and lectotypification of C. elatus var. macronux (Cyperaceae) - Prasad, V. P. (Rheedea, 2014)
Cyperus ohwii Kuk. is excluded from the flora of India and its distribution in Bangladesh is confirmed based on the specimens in CAL and K. The correct nomenclature citation, description and distribution range of the species are provided. Its synonym C. elatus var. macronux is also lectotypified.